Improving students' confidence levels in communicating with patients and introducing students to the importnace of history taking - Halkett, Georgia; McKay, Janice; Shaw, T. (Elsevier, 2010)
Background. Radiographers can have a marked impact on the way patients deal with their illness because they are often one of the first health professionals that patients see. Therefore, it is essential that radiographers have effective communication skills and are able to provide patients with the information they require. The purpose of this study was to test whether the introduction of additional education on communication and history taking improved students’ communication skills. Methods. A short program on communication skills and history taking was introduced to third year undergraduate students prior to a clinical placements period. Three workshops were run; the third included a role play exercise using professional actors as simulated patients. Students completed questionnaires at baseline, following the three workshops and after their subsequent clinical placement. Descriptive statistics were calculated and logistic regression Generalized Estimating Equations models were fitted to test for differences over time in students’ confidence levels.Results. Twenty-seven out of 36 students completed the baseline and final surveys. Students indicated they were highly satisfied with the workshops provided. Statistically significant differences were observed for seven items relating to student’s confidence levels in communicating with patients after they had participated in the workshops and their subsequent clinical placement. Conclusion. The use of communication skills workshops involving actor/patients is an effective method of assisting students to develop their communication and history taking skills. This program has now been implemented into the mentioned undergraduate course and it is recommended that radiography students at other institutions be provided with the opportunity to develop their communication and history taking skills.